Three phase active power filter with selective harmonics elimination - Sozański Krzysztof (Archives of Electrical Engineering, 2016)
This paper describes a three phase shunt active power filter with selective harmonics elimination. The control algorithm is based on a digital filter bank. The moving Discrete Fourier Transformation is used as an analysis filter bank. The correctness of the algorithm has been verified by simulation and experimental research. The paper includes exemplary results of current waveforms and their spectra from a three phase active power filter.